Pengaruh Media Pembelajaran Interaktif Terhadap Hasil Belajar Siswa Kelas IX di MTs Prima Bekasi - Raslina Hanin Safitri; Uza Sukmana; Irvia Eriza (Indo Publishing, 2025)
This research aims to determine whether the use of interactive learning media has an impact on the learning outcomes of Grade IX students at MTs Prima Bekasi. A quantitative research method with a descriptive approach was used. The sample consisted of 40 Grade IX students selected through total sampling. Data were collected using questionnaires to assess students’ perceptions of interactive media usage and its correlation with their academic achievement.The findings revealed a significance value of 0.491 > 0.05, indicating that the influence of interactive learning media on students’ learning outcomes is not statistically significant. The R Square value of 0.013 shows that interactive media accounts for only 1.3% of the variation in students' academic performance, while the remaining 98.7% is attributed to other factors beyond the scope of this study. Therefore, while interactive media can enrich the learning experience, it does not significantly affect learning outcomes in this context.